Radiative-acoustic method of the experimental graduation of receiving piezoelectric transducers in systems of ultrasonic inspection - Kargapol'tsev A. V. (1991, 1991)
The article presents the results of the elaboration of the radiative-acoustic method of graduating piezoelectric transducers based on the use of pulsed beams of charged particles of nanosecond width as source of the calibrating acoustic signals. The article describes the basic technical possibilities of the method and analyzes its special traits which are illustrated by the results of experimental investigations for determining the pulse characteristics of piezoelectric transducers.